The lived experience of stress for parents in the context of COVID‐19–related disruption - Painter, Felicity L.; Booth, Anna T.; Letcher, Primrose; Olsson, Craig A.; McIntosh, Jennifer E. (Family relations, 2023)
Objective This mixed methods study sought to explore the lived experience of stress for parents of young dependent children during COVID‐19 lockdowns in Australia. Background Public health restrictions implemented during the COVID‐19 pandemic disproportionately burdened parents as they balanced novel and competing role demands. Despite growing research on impacts to parent mental health, much less is known about parenting at the experiential level during this period. Method Data were derived from free‐text survey responses collected during 2020 in an Australian population cohort study and analyzed in a mixed methods approach focusing on descriptive phenomenology. Twenty‐eight parent accounts of either ‘extreme’ or ‘minimal’ stress experiences were subject to phenomenological analysis of the individual, interpersonal, and contextual factors associated with each stress category. Results Three themes defined ‘extreme’ stress experiences: inadequacy of resources to cope, perceived lack of control, and compounding stressors. Two themes characterized ‘minimal’ stress experiences: feeling well resourced to cope and the absence of significant disruption to everyday life. Conclusion Findings highlight three targets in particular: compounding stressors, family relationships, and gendered differences in parental stress. Implications Intervention efforts should focus on better resourcing parents experiencing accumulating stressors through provision of individual and relational support and by addressing the higher burden experienced by mothers compared with fathers across pandemic related lockdowns.